Clinical characteristics and outcome of childhood acute promyelocitic leukemia (APL) in Saudi Arabia: a multicenter SAPHOS leukemia group study. Issue 6 (3rd July 2018) - Jastaniah, Wasil; Alsultan, Abdulrahman; Al Daama, Saad; Ballourah, Walid; Bayoumy, Mohamed; Al-Anzi, Faisal; Al Shareef, Omar; Abrar, Mohammed Burhan; Al Sudairy, Reem; Al Ghemlas, Ibrahim
ABSTRACT: Background: Acute promyelocytic leukemia (APL) is a rare form of acute myelogenous leukemia (AML). Survival rates exceed 80% in developed countries. Successful treatments rely on all- trans retinoic acid with anthracycline-based chemotherapy. Availability of modern care and public knowledge play important roles in pediatric APL survival. Method: A cytogenetic diagnosis of APL was confirmed in 30 (14.5%) out of 207 children consecutively diagnosed with de novo AML between January 2005 and December 2012 at nine cancer care centers in Saudi Arabia. Patients were treated based on the standard protocol used by the center following the PETHEMA or the C9710 treatment protocols. We modeled 5-year overall survival (OS), event-free survival (EFS) and cumulative incidence of relapse (CIR) vs. treatment and potential covariates of age at diagnosis, involvement of central nervous system (CNS), and white blood cell (WBC) levels. Results: The median age was 10.4 years with a male:female ratio of 1.9. WBC was 10 × 10 9 /l or greater in 57% and CNS involvement was confirmed in 13%. OS, EFS, and CIR were 74 ± 12%, 55 ± 19%, and, 36 ± 17% respectively. No significant difference was found by treatment protocol. WBC levels were significantly prognostic for all negative events, but treatment with C9710 significantly ameliorated negative WBC effects. Overall outcomes were comparable to those reported in developed countries. Conclusions: Access to modern care is likely to be a critical factor in successful and comparable outcomes of childhood APL across the globe. In the present study, utilizing a cytarabine-containing protocol improved outcome of high-risk pediatric patients with APL.